Chapter Poteri dell'imprenditore e tutele del lavoratore a cinquant'anni dalla legge n. 300/1970 - Voza, Roberto (Studi e saggi, 2022)
Once having reconstructed the founding premises of the concept of subordinate work, as a legal instrument functional to the governance of work in business organization, the essay focuses on the limitation of entrepreneurial powers created by the Workers' Statute to protect worker freedom and dignity and on recent legislative changes introduced by the so-called Jobs Act.